Finding an exercise identity in an older body: “It’s redefining yourself and working out who you are” - Hardcastle, Sarah; Taylor, A. (Elsevier BV, 2005)
Objective: Research has focused on exercise cognitions, including exercise self-identity, physical self-concept, exercise self-schemata and physical self-perceptions as important yet potentially overlapping concepts. Evidence suggests that these constructs help differentiate between physically active and inactive individuals, and also change in response to exercise programmes. Further qualitative research is needed to understand how a physical activity intervention for inactive older individuals influences physical self-cognitions over time. Method: Interpretivist study employing semi-structured, repeated interviews to identify changes in exercise cognitions. Fifteen women (43–77 years) were interviewed at various points both during and following their primary care referral to a 10 week community exercise intervention. Data were subsequently used from eight participants who provided particularly rich data. Results: Many of the women in this study demonstrated a change in their sense of exercise identity over time. The results reflected themes of the meaning of an exercise identity, influences on developing an exercise identity, “it gets you back into life”, and, time to change self-cognitions. Mechanisms implicated in developing an exercise identity included feelings of achievement, control, a sense of belonging, and social interaction. In time, the participants noted changes in social (caring) and domestic (physical activity) priorities: guilt-free exercise sessions became part of their weekly routines. The additional identity as an exerciser was associated with feelings of empowerment and well being. Conclusion: This qualitative approach provides new findings on how middle aged and older women build an exercise identity and resolve conflict with respect to competing roles and identities.